Effect of Different Placement Techniques on Microleakage of Class V Composite Restorations - M. Moezyzadeh; M. Kazemipoor (Tehran University of Medical Sciences, 2009)
Objective: Various techniques of composite placement have been used to decrease microleakage around the composite restorations. Due to controversial results, the present study was conducted to investigate the effect of different placement techniques on microleakage in class V composite restorations. Materials and Methods: Sixty class V cavities were prepared on the buccal and lingual surfaces of 30 extracted healthy human premolars. The teeth were randomly assigned to five groups, and were restored with composite resin, using five different techniques: (1) horizontal increments (gingivo-occlusal), (2) horizontal increments (occluso-gingival), (3) oblique increments (gingivo-occlusal), (4) oblique increments (occluso-gingival), and (5) bulk placement. After thermocycling, 500 cycles of between 5°C and 55°C (SD=2), and immersion in 0.5% alcoholic Fuschin, the teeth were then sectioned and evaluated for microleakage by stereomicroscope (×16). Microleakage was scored on a 0-4 scale. Nonparametric Mann-Whitney U and Kruskal-Wallis tests served for statistical analysis. Results: Gingival margins of class V cavities showed microleakage regardless of the placement technique. Oblique (gingivo-occlusal) technique showed less microleakage in gingival margins of the restorations compared to bulk technique. The least microleakage in gingival margins was related to group 3 while the most microleakage was related to group 5. Bulk and oblique (gingivo-occlusal) incremental techniques produced significantly different rate of microleakage (P<0.003). Group 3 showed the most difference with groups 5, 1, 2, and 4, respectively. Conclusion: Among four incremental techniques, the gingivo-occlusal oblique filling technique resulted in a lower leakage value, when compared to the bulk filling technique.